Quantitative standards that support the decision to choose enterprise product distribution channels Hodna Mills M'sila - Achour Beddar; Abderrahmane Elguerri (Dirassat Journal Economic Issue, 2020)
The sales function is at the forefront of the various administrative functions, which requires attention to efficient and effective management, through the use of modern quantitative methods of management, and the proper implementation of the marketing strategy requires the follow-up and development of various elements related to the policy of sales and control, Weak marketing activity.One of the most prominent policies with a clear need to use quantitative methods to improve them is distribution policy related to the products of the organization within the distribution channels, which means that the tools of the quantitative approach should be used to rationalize the decisions of distributing the products of the organization within the distribution channels of its products.By following the quantitative approach in the sales policy of the incubator mills, we find that the quantitative model has an effective role in selecting the distribution channels of the products of the institution, which contributes to improving the policy of distributing the products of the institution and implementing the planned strategy.